Effectiveness Of Defoliants - Ubaydullayev Madaminjon Mo’minjonovich; Babayeva Malikakhon Nabijon qizi (Genius Journals, 2022)
The foreign Ento Dephol showed a hig h result when cotton c a uses open 30 40% while using 0.20 0 litres of defoliation for each hectar e in order to defoliate cotton artificia lly 7.0 litres use of defoliation gave better result regarding the other alternatives.
Keywords: Types Of Defoliation And Defoliants; Cotton Leaves Dry And Semi Dry Leaves.